Resilience and Veteran Community Reintegration: An Exploratory Study. (2nd October 2019) - Castillo, Elmer A.; Mason, Justin; D'Addario, Aaron; Chow, Graig M.; Tenenbaum, Gershon
Abstract: The purpose of this study was to explore the potential association between resilience and veteran community reintegration (VCR) in recently discharged military veterans. It was hypothesized that higher resilience levels, as measured by the Response to Stressful Experiences Scale (RSES), would be associated with lower perceived difficulties with VCR, as measured by the Military to Civilian Questionnaire (M2C-Q). In addition, specific demographic and military experience variables were hypothesized to predict resilience levels and VCR outcomes. An online survey was developed and disseminated via social media and in-person at local student veteran centers. A total of 45 participants completed the survey. A multiple regression analysis indicated that 29.7% of the total variance on the M2C-Q was accounted for by RSES scores and time out-of-service. Applied implications and future directions are discussed.